2019
DOI: 10.1371/journal.pntd.0007336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ‘The Vicious Worm’ educational tool on Taenia solium knowledge retention in Zambian primary school students after one year

Abstract: Background Taenia solium is a neglected zoonotic parasite endemic throughout many low-income countries worldwide, including Zambia, where it causes human and pig diseases with high health and socioeconomic burdens. Lack of knowledge is a recognized risk factor, and consequently targeted health educational programs can decrease parasite transmission and disease occurrence in endemic areas. Preliminary assessment of the computer-based education program ‘The Vicious Worm’ in rural area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Previous T . solium health education interventions in India [ 22 ], Kenya [ 23 ], Mexico [ 24 ], Tanzania [ 20 , 25 – 29 ] and Zambia [ 30 , 31 ] led to significant increases in knowledge among targeted stakeholders. Moreover, attitudinal and behavioral change were reported in different T .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous T . solium health education interventions in India [ 22 ], Kenya [ 23 ], Mexico [ 24 ], Tanzania [ 20 , 25 – 29 ] and Zambia [ 30 , 31 ] led to significant increases in knowledge among targeted stakeholders. Moreover, attitudinal and behavioral change were reported in different T .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, attitudinal and behavioral change were reported in different T . solium health education studies; including increased condemnation of infected meat, better confinement of pigs and improved sanitary/hygienic practices [ 20 , 22 25 , 27 30 , 32 ]. More importantly, health education proved able to reduce PCC [ 20 , 24 , 25 ] and HCC [ 32 ] incidence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated a statistically significant increase in knowledge and attitudes scores in both the United Republic of Tanzania and Zambia. 10,11 In Peru, mechanisms for transferring intervention strategies to local communities, such as community-based reporting of pig cysticercosis to inform ring strategies, have also been explored. 12 While this study did not identify a significant change in the seroincidence of cysticercosis in the intervention group, efforts to develop locally sustainable interventions, for example, by transferring ownership of interventions, is important.…”
Section: Policy and Practicementioning
confidence: 99%